The role of Ta on twinnability in nanocrystalline Cu–Ta alloys. Issue 1 (2nd January 2017) - Bhatia, M. A.; Rajagopalan, M.; Darling, K. A.; Tschopp, M. A.; Solanki, K. N.
ABSTRACT: Nanostructured Cu–Ta alloys show promise as high-strength materials in part due to their limited grain growth. In the present study, we elucidate the role of Ta on the transition from deformation twinning to dislocation-mediated slip mechanisms in nanocrystalline Cu through atomistic simulations and transmission electron microscopy characterization. In particular, computed generalized stacking fault energy curves show that as Ta content increases there is a shift from twinning to slip-dominated deformation mechanisms. Furthermore, heterogeneous twinnability from microstructural defects decreases with an increase in Ta. The computed effect of Ta on plasticity is consistent with the HRTEM observations. GRAPHICAL ABSTRACT: IMPACT STATEMENT We show for the first time using atomistic simulations and TEM that, similar to grain size, the Tanano-particles can be used to tailor the governing deformation mechanisms in NC-alloys.